Perceptions and experiences of female partners of clients of voluntary medical male circumcision in Harare, Zimbabwe - Mazambara, Fine (My University, 2017)
Introduction Zimbabwe is lagging behind on its target to scale up Voluntary Medical Male Circumcision (VMMC). The engagement of female partners in VMMC demand creation is important as they can play an important role in their male partners’ decision to uptake VMMC. Exploring women’s perceptions and experiences will help to better understand factors behind low uptake of VMMC in Zimbabwe as efforts are being made to scale up VMMC for HIV prevention. The aim of the study was to explore female partners’ underlying perceptions and experiences of having their partners undergo medical male circumcision in order to inform the development of promotional messages on the basis of women’s experiences with VMMC. Methods The study was conducted in Mbare, an urban high density suburb in the southern district of Harare utilising qualitative methodology. Individual in-depth interviews were conducted using an in-depth interview guide. Through purposive sampling a total of twenty female partners of medically circumcised men attending antenatal clinic between February and May 2016 were recruited. Interviews were audio recorded and transcripts were analysed using content analysis. Results The results show that women were knowledgeable about VMMC. The perception towards medical male circumcision was linked to the perceived benefits of VMMC. The main role that women played was encouraging their male partners. The perception of women towards VMMC was generally good. The perceived benefits of having a circumcised partner were Fine Mazambara 872453 iv reduced risk of HIV and STIs, improved sexual experience, improved hygiene, improved sexual communication, no need to use condoms and improvement of the relationship. The risk perception towards HIV and STIs was decreased after the male partner’s VMMC and fear of risk compensation was reported. Women had misconceptions about adverse events of circumcision and the age at which men can be circumcised. Mass media was the main source of VMMC information for women. VMMC was understood to offer direct protection from HIV for women and circumcised men were understood to being conferred full protection from HIV and STIs. Conclusions Women have knowledge on VMMC although their knowledge on adverse events associated with circumcision, age at which men can be circumcised, indirect protection for women, and partial protection for men can be improved. The perceptions of women towards VMMC were influenced by the perceived benefits of having a circumcised partner. The main perceived benefits of having a VMMC client as a male partner is reduced risk of HIV and STIs and improved sexual experience. Targeted health messages directed at women should therefore aim at increasing women’s knowledge of VMMC, include improved sexual experience and take gender issues into consideration.
A research submitted to the faculty of health science (School of Public Health), University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Masters in Public Health in the field of Social and Behaviour Change Communication. October 2017.
Keywords: Circumcision, Male; Sexually Transmitted Diseases; HIV